Cereal pests among nest parasites – the story of barley thrips, Limothrips denticornis Haliday (Thysanoptera: Thripidae) - Fedor, Peter; Doričová, Martina; Dubovský, Michal; Kisel'ák, Jozef; Zvarík, Milan (Entomologica Fennica, 2011)
Barley thrips, Limothrips denticornis, Haliday, 1836 (Thysanoptera: Thripidae), a grass-dwelling Holarctic species represents a model example to study transport mechanisms of Thysanoptera into nests. In samples from more than 1,500 nests, barley thrips were recorded in nests of 20 vertebrate species, both birds and mammals. Applying appropriate statistics (nonparametric methods) clear clustering among nest materials and a strong relationship between presence of thrips and grass as the nest material was found. Occurrence of thrips was not associated with nest size, location or height. To validate our statistical analyses 15 wooden boxes were installed and equipped with sticky traps to record the whole year migration dynamics. Barley thrips infiltrate nests by various ways (e. g. dwelling on bark, landing from atmosphere), however most of them (88%) invade passively on nest material (grass) in spring (1st summer nesting) and autumn (winter nest building).